STRATEGY FOR IMPLEMENTING AND DEVELOPING SMART CITY IN ORDER TO REFORM LOCAL GOVERNMENT BUREAUCRACY IN CIMAHI CITY - Titin Rohayatin; Zaenal Abidin As; Harky Ristala; Neneng Mastoah (Jurnal Academia Praja, 2022)
A Smart City is a concept for urban development that incorporates information and communication technology (ICT) and Internet of Things (IoT) technologies. A smart city aims to maximize service efficiency via the use of informatics and technology. Data gathered from people and devices is then processed and evaluated using sensors that are coupled with a real-time monitoring system. This data is gathered as critical data to help the community overcome the inefficiencies of bureaucratic services. The rapid advancement of information and communication technology, combined with the development of an increasingly reliant society on the performance of the government bureaucracy, generally requires the government's strategy for implementing and developing Smart Cities. because it has the potential to significantly influence lives, both personally and collectively, including those of government agencies. However, several difficulties remain in its implementation, preventing the government's strategy from being executed properly. The government's strategy for implementing and developing the E-government idea, as well as for applying and developing the Smart City concept to achieve bureaucratic reform, is highly suitable for use as a form of assistance for the development of high-quality community services. The Smart City idea is being implemented in Cimahi City using the following six indicators: (1) smart government, (2) smart economy, (3) smart environment, (4) smart living, (5) smart people, and (6) smart mobility are all examples of smart concepts.